Iran-Saudi Arabia Rivalry and the Yemen Crisis - Ramazan İZOL (Gazi Akademik Bakış)
Iran's confrontation with the USA and its allies within the framework of its revolutionary Islamic identity has led many Arab countries, especially Saudi Arabia, to be vigilant. After the 1979 Iranian Revolution, the relations between Iran and Saudi Arabia deteriorated fundamentally, and the ideological and geopolitical struggle between the two countries deepened. This situation not only affected the two countries, but also drew many countries in the region to the firing line. While regional instability has increased in the Middle East, sectarian rivalry and ideological struggle have also escalated. The Arab Spring process, on the other hand, made the Hobbesian anarchic structure among the Middle Eastern states even more evident. In this respect, after the Arab Spring, an axis of tension has emerged between Iran and Saudi Arabia, covering countries such as Yemen, Syria, Lebanon, Iraq and Bahrain. The hottest point of this tension axis has been Yemen. As a matter of fact, the progress of the Zaydi Houthis, known as Shiite, in Yemen was supported by Iran, but was found unacceptable by Saudi Arabia and its allies. Ultimately, Saudi Arabia and its allies started a struggle against the Houthis, which they saw as part of Shiite expansionism. On the other hand, with the aggressive policy of Saudi Arabia towards them, the Houthis have further developed their relations with Iran for pragmatic and ideological reasons. In essence, the Houthis, which emerged as a result of Yemen's local and social problems, gradually became another denominator in the equation of the Iran-Saudi Arabia rivalry.